Desempenho das metodologias convencionais de quantificacao de reservas<>9d\estudo de um deposito de niquel - Batista, J. J.; Angeli, N. (My University, 1988)
Ten working-groups were formed for estimation of nickel ore reserves, associated to an ultrabasic body, at Ipanema, MG. Each group employed six methods: parallel sections, isolines, triangles, polygons, blocks and statistical method. The triangles method showed more variability, and the smallest dispersion was obtained by the polygons method; the other methods induced fluctuations in relation to the mean. Top and bottom ore irregularities produced difficulties in the performance of the parallel sections method. Different ways of application of isolines method also produced some variations. Excepting for few calculated data, the overall results are very close to 2 200 000 t or ore. -English summary
Methodologies applied to ore quantification: a nickel ore case study
Keywords: nickel; ore reserve estimation; Brazil, Ipanema